"Transfer of change" and large group intervention methods (LGIMs): a call for research on a neglected topic in organizational change literature. Issue 1 (2nd January 2018) - November, Eben David
Abstract : Purpose: The purpose of this paper is to highlight the gap in organizational change literature in general and the large group interactive method (LGIM) literature in particular. Design/methodology/approach: By comparing LGIM and training literature studies, the absence of a concept in the former literature parallel to the well-known concept of "transfer of training" is highlighted. The concept of the transfer of change is introduced to address this gap. Findings: This paper suggests that the transfer of change is as important to the success of organizational change initiatives as transfer of training is to the success of training programs. Originality/value: This paper is the first to introduce the concept of transfer of change to the organizational change and LGIM literature studies. Furthermore, a tentative research agenda regarding transfer of change and LGIMs is presented. Therefore, the paper is a valuable resource for researchers who study organizational change initiatives in general and LGIMs in particular.